Multicriteria optimization model for supply process problem under provision and demand uncertainty - Rodriguez, Maria Analia (2011)
Supply processes play an important role in customer satisfaction and company costs. The main characteristics of this problem are given by several decisions that follow a hierarchical structure and a very uncertain context, conditioning the success of the solutions proposed. Two significant sources of uncertainty are considered in this work, namely, provision and demand, both modeled as exogenous variables with random behavior. An optimization model is formulated to reduce the effects of the uncertainty in the company supply process. Because of the problem complexity, a multicriteria model is required to bring a comprehensive solution. Several Pareto-optimal solutions are obtained through application of the ε-constraint technique. The original formulation is a nonconvex one that is then transformed to obtain a disjunctive linear model that guarantees a global result.